2022
DOI: 10.1177/13567667221109267
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and outcomes of use experience of airport service robot: The stimulus-organism-response (S-O-R) framework

Abstract: This study empirically explores passengers’ emotional experience of using airport service robots from the perspective of the stimulus-organism-response (S-O-R) framework. Our proposed model hypothesizes that stimuli, which is the functional value and coolness of using the airport service robots, leads to satisfaction and influences responses such as perceived smartness and word-of-mouth of the airport. A survey sample of 321 respondents with use experience of airport service robot were employed for the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Theoretically, this study reinforced the utility of S-O-R theory for explaining the underpinnings of patronage behaviour. The S-O-R have been widely used in traditional consumer behaviour research (Peng and Kim, 2014;Chen and Girish, 2022); however, its utility in online consumer behaviour research is yet to be fully established especially for explaining undergraduate cohort online consumer behaviour. Hence, this study extends the utility of the S-O-R theory as it not only guided the development of the study's conceptual framework; but also provide insights and better understanding into the psychographic dynamics of online choice behaviour of the fast-expanding GenZ segment in Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, this study reinforced the utility of S-O-R theory for explaining the underpinnings of patronage behaviour. The S-O-R have been widely used in traditional consumer behaviour research (Peng and Kim, 2014;Chen and Girish, 2022); however, its utility in online consumer behaviour research is yet to be fully established especially for explaining undergraduate cohort online consumer behaviour. Hence, this study extends the utility of the S-O-R theory as it not only guided the development of the study's conceptual framework; but also provide insights and better understanding into the psychographic dynamics of online choice behaviour of the fast-expanding GenZ segment in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…It is the cognitive and affective interim state of e-shopper. Thus, the schema argues that stimuli (i.e., the six inhibitors being external input from exposed environment as perceived by an individual) can trigger a response (i.e., resulting behaviour that manifest in form of online patronage) via the organism's internal evaluation process depicted as EI Chen and Girish, 2022).…”
Section: Research Schema: the Nexus With Theorymentioning
confidence: 99%
“…However, in organism, most previous studies have emphasized the psychological factors of intrinsic cognition. Although it is effective to show that stimulus is converted into explicit responses through intrinsic transformation, it should be expressed in subsequent usage attitude [ 30 ]. The continuous intention to use of English M-learning depends on students' usage attitudes on English M-learning and self-efficacy [ 26 , 31 , 32 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chi et al [31] investigated customers' acceptance of artificially intelligent service robots, and they found that the crucial roles of perceived social influence, hedonic motivation, and anthropomorphism comprise customer acceptance behavior. Chen and VG [32] studied the antecedents and outcomes of users' experiences with airport service robots, and they demonstrated that service satisfaction forms perceived smartness and word-of-mouth intentions. There are still limited studies on the experience economy of robot services.…”
Section: Robot Services In the Hospitality Sectormentioning
confidence: 99%
“…In other words, customers enjoy watching and experiencing a situation, which makes it an entertaining experience. Third, education is classified as active participation and absorption, and it aims to satisfy the desire to obtain information or knowledge that was previously unknown or desired to be known [9,32]. It is an active experience, because customers actively participate in a specific situation, which is unlike the entertainment experience.…”
Section: The Experience Economymentioning
confidence: 99%